2006
DOI: 10.2495/cr060591
|View full text |Cite
|
Sign up to set email alerts
|

A new idea for train scheduling using ant colony optimization

Abstract: This paper develops a new algorithm to the train scheduling problem using Ant Colony System (ACS) meta-heuristic. At first, a mathematical model for a kind of train scheduling problem is developed and then the algorithm based on the meta-heuristic is presented to solve the problem. The problem is considered as a traveling salesman problem (TSP) wherein cities represent the trains. ACS determines the sequence of trains dispatched on the graph of the TSP. Based on the sequence obtained and removing for collision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…[10] Power-system modification reversible substation installing [12] different areas of implementation different approaches discussion-review article [13] different areas of implementation different approaches discussion-review article [14] Power-system modification on-board energy storage device (ESD) using [15] Power-system modification on-board hybrid accumulation system using [16] power system modification electricity recovery regeneration, use of energy storage, train control and optimisation, and operational effects [17] power-system modification stationary energy storage system [18] power-system modification, electricity recovery, speed profile optimisation on-board energy storage device, optimal design of Automatic Train Operation system speed profiles [19] speed-profile optimisation multi-step decision problem, Dynamic Programming [20] speed-profile optimisation using the coasting technique; algorithm [21] speed-profile optimisation meta-heuristic, traveling salesman problem approach, Ant Colony Optimization [22] speed-profile optimisation Ant Colony Optimization [23] speed-profile optimisation multi-objective and multi-disciplinary optimisation modeFRONTIER [24] speed-profile optimisation numerical algorithm for the optimal driving solution [25] speed-profile optimisation Matlab implementation of the Simulated Annealing optimisation algorithm [26] speed-profile optimisation multi-objective hybrid optimization algorithm using a comprehensive learning strategy (ICLHOA) [27] electricity recovery a 'time slot and energy grid' model implementation; the running time of trains in sections, the dwell time of trains at stations and the headway can be adjusted [28] electricity recovery train's dynamics microsimulation [29] electricity recovery particle swarm optimisation algorithm [30] electricity recovery genetic algorithm implementing integrated Energy-efficient Operation Methodology (EOM) [31] electricity recovery the mathematical programming optimization model [32] electricity recovery microscopic passenger-centric models; proposed several fast heuristic methods…”
Section: Publication Implementation Area Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Power-system modification reversible substation installing [12] different areas of implementation different approaches discussion-review article [13] different areas of implementation different approaches discussion-review article [14] Power-system modification on-board energy storage device (ESD) using [15] Power-system modification on-board hybrid accumulation system using [16] power system modification electricity recovery regeneration, use of energy storage, train control and optimisation, and operational effects [17] power-system modification stationary energy storage system [18] power-system modification, electricity recovery, speed profile optimisation on-board energy storage device, optimal design of Automatic Train Operation system speed profiles [19] speed-profile optimisation multi-step decision problem, Dynamic Programming [20] speed-profile optimisation using the coasting technique; algorithm [21] speed-profile optimisation meta-heuristic, traveling salesman problem approach, Ant Colony Optimization [22] speed-profile optimisation Ant Colony Optimization [23] speed-profile optimisation multi-objective and multi-disciplinary optimisation modeFRONTIER [24] speed-profile optimisation numerical algorithm for the optimal driving solution [25] speed-profile optimisation Matlab implementation of the Simulated Annealing optimisation algorithm [26] speed-profile optimisation multi-objective hybrid optimization algorithm using a comprehensive learning strategy (ICLHOA) [27] electricity recovery a 'time slot and energy grid' model implementation; the running time of trains in sections, the dwell time of trains at stations and the headway can be adjusted [28] electricity recovery train's dynamics microsimulation [29] electricity recovery particle swarm optimisation algorithm [30] electricity recovery genetic algorithm implementing integrated Energy-efficient Operation Methodology (EOM) [31] electricity recovery the mathematical programming optimization model [32] electricity recovery microscopic passenger-centric models; proposed several fast heuristic methods…”
Section: Publication Implementation Area Methodsmentioning
confidence: 99%
“…In refs. [21,22], the authors propose the application of the Ant Colony Algorithm to the train scheduling optimization problem. Ref.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some algorithms of the metaheuristics method include genetic algorithm [1], neural networks [2], tabu search [3], simulation annealing [4] and ACO [5]. Although the solution quality of these algorithms is high, there is still little research on passenger and freight train scheduling problem on doubletrack railway line.…”
Section: Introductionmentioning
confidence: 99%
“…Dorigo and Gambardella [7] showed that the ACS algorithm has been more successful than the other metaheuristics in solving the TSP. K. Ghoseiri [5] has successfully developed the ACS algorithm applied in the single-track railway line. But until now, nobody consider the passenger and freight train scheduling problem in double-track railway line which has the different solution method with the problem in singletrack line.…”
Section: Introductionmentioning
confidence: 99%